Child Growth, Shocks, and Food Aid in Rural Ethiopia - Yamano, Takashi; Alderman, Harold; Christiaensen, Luc (World Bank, Washington, DC, 2014)
Over the past decades child stunting in Ethiopia has persisted at alarming rates. While the country experienced several droughts during this period, it also received enormous amounts of food aid, leading some to question the effectiveness of food aid in reducing child malnutrition. Using nationally representative household surveys from 1995-96 and controlling for program placement, Yamano, Alderman, and Christiaensen find that children between 6 and 24 months experienced about 0.9 cm less growth over a six-month period in communities where half the crop area was damaged compared with those without crop damage. Food aid was also found to have a substantial effect on the growth of children in this age group. And on average, the total amount of food aid appeared to be sufficient to protect children against plot damage, an encouraging sign that food aid can act as an effective insurance mechanism, though its cost-effectiveness needs further investigation.